YIELDS AND DOMINANCES OF MICRO-VEGETATION IN FOREST-STEPPE PASTURE NEARBY A POPULATION CENTER OF MONGOLIA - Chuluunbat, G; Zolzaya, S; Baasanjalbuu, B; Yamasaki, S (Mongolian Journal of Agricultural Sciences, 2015)
A study was conducted in 2011 and 2012 on a forest-steppe pasture in danger of pasture degradation to determine pasture yields and plant dominances from differences in micro-vegetation, with the aim of contributing to conservation and effective utilization. In the pastures, two different micro-vegetation located conterminously were observed based on their topographies and coverage by dominant plant species: Site 1 (S1) on a hillside where Poa or grasses and herbs equally dominated and Site 2 (S2) in a pocket where herbs predominated followed by Poa or grasses. Yield was significantly increased from June to August, but decreased by October in both the sites in each year (p < 0.001). The yields in S2 were significantly (p < 0.001) or tended to be higher than those in S1 during all study periods. The relative summed dominance ratio (R-SDR2) of the grass was higher in S2 (34.0%) than in S1 (18.4%), and that of herbs was higher in S1 (64.2%) than in S2 (51.8%). It was concluded that R-SDR2 is a potential indicator of pasture condition, and that the proportion of grasses increase while that of herbs decrease as a pasture is well conserved and/or managed. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 117-123